Evolution of IFN-λ in tetrapod vertebrates and its functional characterization in green anole lizard (Anolis carolinensis). (August 2016) - Chen, Shan Nan; Zhang, Xiao Wen; Li, Li; Ruan, Bai Ye; Huang, Bei; Huang, Wen Shu; Zou, Peng Fei; Fu, Jian Ping; Zhao, Li Juan; Li, Nan; Nie, Pin
Abstract: IFN-λ (IFNL), i.e. type III IFN genes were found in a conserved gene locus in tetrapod vertebrates. But, a unique locus containing IFNL was found in avian. In turtle and crocodile, IFNL genes were distributed in these two separate loci. As revealed in phylogenetic trees, IFN-λs in these two different loci and other amniotes were grouped into two different clades. The conservation in gene presence and gene locus was also observed for the receptors of IFN-λ, IFN-λR1 and IL-10RB in tetrapods. It is further revealed that in North American green anole lizard Anolis carolinensis, a single IFNL gene was situated collinearly in the conserved locus as in other tetrapods, together with its receptors IFN-λR1 and IL-10RB also identified in this study. The IFN-λ and its receptors were expressed in all examined organs/tissues, and their expression was stimulated following the injection of polyI:polyC. The ISREs in promoter of IFN-λ in lizard were responsible to IRF3 as demonstrated using luciferase report system, and IFN-λ in lizard functioned through the receptors, IFN-λR1 and IL-10RB, as the up-regulation of ISGs was observed in ligand-receptor transfected, and also in recombinant IFN-λ stimulated, cell lines. Taken together, it is concluded that the mechanisms involved in type III IFN ligand-receptor system, and in its signalling pathway and its down-stream genes may be conserved in green anole lizard, and may even be so in tetrapods from xenopus to human. Highlights: Lizard contains only one IFNL locus, while turtle and crocodile have two loci. Homologues of human IFNL4 gene may exist widely in mammal lineage. Amniote IFNL genes can be grouped into two clades in phylogenetic tree. Lizard IFNL promoter report plasmid can be activated by lizard IRF3. Lizard IFNL and its receptors IFNLR1 and IL10RB are functional in expression of ISGs.